Impact of climate services on the operational decision of Murrah buffalo farmers in Haryana - MAITI, Manjunath K V, D Anil Kumar Reddy, Sanchita Garai, H R Meena, Raj Kumar, Mukesh Bhakat, Goutam Mondal, Anjali Aggarwal; Sanjit Maiti (Indian Journal of Dairy Science, 2024)
Global warming and its concomitant changes in mean climate variables and climate variability have an impact on animal feed and fodder, animal health, production, and water availability. Buffaloes are the mainstay of the Indian dairy economy and the backbone of the rural economy and dairy industry in the Haryana state in particular. Murrah buffalo-based production system has to be imparted the ability to withstand the adversities associated with climate change as well as to maintain their productivity. Therefore, the present study was undertaken to develop climate services and analyze their impact on Murrah buffalo farmers’ operational decision-making related to dairy farming. The study was conducted in the Hisar, Jind, and Rohtak districts of Haryana state. Two blocks were selected randomly from each district and from each block three experimental villages and one control village were selected, resulting in 18 experimental and 6 control villages in total. The three experimental villages of each block were randomly assigned to the intervention mode of either WhatsApp, Text SMS, and Mobile application which was exclusively developed for the present study thus resulting in 6 villages each receiving treatment through WhatsApp, Text SMS, and Mobile application. From each village, 15 farmers were selected randomly and provided with treatment i.e., weekly THI-based Murrah buffalo climate service module. The findings of the study revealed a positive treatment effect of the climate services on various practices like the adoption of improved varieties of fodder, and nutrition management through the inclusion of oilcake, miner mixture in animal diets. The adoption of rubber mats, providing chopped fodder, use of bedding materials and covering open spaces of the animal shed during winter, the practice of deworming the herd and maintenance of cattle shed hygiene, and others. Hence, the climate services for Murrah buffalo farmers were found to be a potential adaptation tool to enhance the resilience capacity of vulnerable dairy farmers to adapt to climate change.